2015
DOI: 10.3390/nu7085306
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Vitamin K Intake Is Associated with Cognition and Behaviour among Geriatric Patients: The CLIP Study

Abstract: Our objective was to determine whether dietary vitamin K intake was associated with cognition and behavior among older adults. 192 consecutive participants ≥65 years, recruited in the cross-sectional CLIP (Cognition and LIPophilic vitamins) study, were separated into two groups according to the tertiles of dietary phylloquinone intake (i.e., lowest third below 207 µg/day versus the other two thirds combined). Daily dietary phylloquinone intake was estimated from 50-item interviewer-administered food frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 30 publications
2
38
0
3
Order By: Relevance
“…8,9 A subsequent study by Presse and colleagues revealed that in cognitively intact elderly individuals, higher serum phylloquinone concentrations were correlated with enhanced verbal episodic memory and recollection tests. 10 More recently, studies of older adults have reported better cognitive function and behavioural rating among those in the highest quartile of dietary phylloquinone intake 11 and fewer and less severe subjective memory complaints among those with higher dietary intakes. 12 These findings however appear to be confined to older populations.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 A subsequent study by Presse and colleagues revealed that in cognitively intact elderly individuals, higher serum phylloquinone concentrations were correlated with enhanced verbal episodic memory and recollection tests. 10 More recently, studies of older adults have reported better cognitive function and behavioural rating among those in the highest quartile of dietary phylloquinone intake 11 and fewer and less severe subjective memory complaints among those with higher dietary intakes. 12 These findings however appear to be confined to older populations.…”
Section: Introductionmentioning
confidence: 99%
“…Rats fed with a low vitamin K diet presented an altered sphingolipid profile in their hippocampus, which is the key cerebral region for memory [13]. Clinical studies on human subjects confirmed a positive association between, on the one hand, serum concentrations and dietary intake of vitamin K and, on the other hand, cognitive outcomes in healthy elderly [14][15][16]. e large number of geriatric patients on OAT has suggested the need for further investigations so as to understand whether treatments with any vitamin K antagonists may affect cognitive functions.…”
Section: Discussionmentioning
confidence: 83%
“…e role of vitamin K in coagulation processes has been extensively studied and characterised [29]. Recent studies have suggested that the vitamin may also play a key role in cognitive performance [13][14][15][16]. Studies on animal models have suggested that vitamin K may be involved in memory consolidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, in addition to its role in blood coagulation, vitamin K is also involved in brain health and function [3] by regulating the synthesis of sphingolipids, a constituent of the myelin sheath and neuronal membrane [4], and the biological activation of vitamin K-dependent proteins (VKDPs) involved in neuron physiology and survival [4]. Epidemiological data support a positive association between serum vitamin K concentration and episodic memory function in older adults [5]; decreased dietary vitamin K intakes were also associated with more pronounced cognitive and behavioural disorders [6]. …”
Section: Introductionmentioning
confidence: 99%